2018
DOI: 10.1016/j.athoracsur.2017.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Thoracoscopy Versus Thoracotomy Not Just Technique Dependent: A Study of 9,787 Patients

Abstract: Numerous patient- and hospital-related variables that affect morbidity and mortality also affect whether a patient undergoes VATS or open lung resection. Studies evaluating VATS must account more accurately for selection bias and adjust for these confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Treatment outcomes extracted from SPARCS included complications and in-hospital mortality. Complications were identified by diagnosis codes and categorized as cardiovascular, pulmonary, infectious, and intraoperative, following a previously published approach [19,20]. All corresponding ICD-9 codes are provided in the Supplemental Tables 1 and 2.…”
Section: Patient Datamentioning
confidence: 99%
“…Treatment outcomes extracted from SPARCS included complications and in-hospital mortality. Complications were identified by diagnosis codes and categorized as cardiovascular, pulmonary, infectious, and intraoperative, following a previously published approach [19,20]. All corresponding ICD-9 codes are provided in the Supplemental Tables 1 and 2.…”
Section: Patient Datamentioning
confidence: 99%
“…Some adverse events are rare in the modern era (ie, 1% operative mortality rates [57]) limiting the power to compare outcomes even with the use of large population-based datasets. Retrospective studies comparing VATS and thoracotomy suggest noninferiority of VATS [18,24,58], morbidity [24,25,27,59,60], LOS [18,24,28,59], and costs [18,44]. Randomized trials show no evidence of a difference in morbidity, mortality, or LOS between VATS and open lobectomy [29,30,61].…”
Section: Evidence Base For Vats Lobectomymentioning
confidence: 99%
“…Dr Wolf and colleagues [1] add to an ever growing body of literature that compares outcomes between thoracotomy and a video-assisted thoracoscopic surgical (VATS) approach to lobar and sublobar resection. They hypothesized that there would be no relationship between VATS and outcomes after adequately controlling for selection bias.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Most retrospective and single-institution studies show an association between VATS and better short-term outcomes. However, Wolf and colleagues [1] provide citations for studies in which there is no association between VATS and short-term outcomes. In addition, a recent prospective study from Memorial Sloan-Kettering showed no evidence of a relationship between VATS and patient-reported health-related quality-of-life or pain scores at 12 months.…”
Section: Invited Commentarymentioning
confidence: 99%